Hubungan antara perawatan payudara dengan pengeluaran colostrum pada kehamilan trimester III - Lidia Widia (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
The high number of pregnant women who do not breast care during pregnancy, after childbirth will then encountered problems that harm the mother and the baby. The aim of research to find out if there is a relationship between breast care expenditure colostrum in the third trimester of pregnancy. The research method using the analytic survey with cross sectional approach. The primary data obtained with tools questionnaire answered by all respondents amounted to 29 people. Sampling technique using total sampling, data analysis techniques using Chi-Square. The results of the analysis we found the majority of respondents do breast care, and the majority of respondents spending colostrum. P values obtained value 0,002 0,05 so Ho rejected, so that there is a very close relationship between breast care expenditure colostrum in the third trimester of pregnancy. The conclusion of this study there is a very close relationship between breast care expenditure colostrum in the third trimester of pregnancy on Poskesdes Kampung Baru. Expected health workers provide counseling to pregnant women about breast care so that colostrum can get out.